An approximate isotropic perfectly plastic solution for compressive strength of geosynthetic-reinforced soil. Issue 5 (1st October 2004) - Tatsuoka, F.
Abstract : A closed-form approximate solution, based on the stress characteristics method, for the compressive strength of a cohesionless soil mass reinforced with multiple horizontally arranged geosynthetic reinforcement layers subjected to vertical load through rigid platens is presented. It is assumed that the stress–strain properties of the backfill are isotropic perfectly plastic, the friction angle at the interface between the backfill and the reinforcement is uniform, and the effects of the weight of the backfill can be ignored. Assuming that the length/height ratio of the respective soil layer, sandwiched by reinforcement layers, is sufficiently large, then several other simplifications are introduced in the numerical procedures. The solution is compared with the results of plane strain compression tests using large specimens of air-dried Toyoura sand reinforced with multiple layers of a polymer geogrid. The equivalent friction angles at the interface between the sand and the geogrid, treated as a platen having a 100% coverage ratio, which were previously back-calculated using a non-linear FEM analysis by the author, were used in the present approximate analysis. It is shown that, with known values of the angle of friction of the backfill and the interface friction angle, the compressive strength of a given reinforced soil mass can be estimated reasonably well.